Re-desain Interior Co-working Space SUB Co Spazio dengan Pendekatan Ekologi Interior di Surabaya - Wijaya, Jason Marcellinus; Audrey, Eugenia - (Universitas Pembangunan Jaya, 2024)
Abstract — Co-working spaces have emerged as a popular solution for individuals and companies seeking dynamic work environments. However, the SUB Co Spazio co-working space in Surabaya faces challenges regarding comfort and conducive working conditions. Insufficient supporting facilities, inadequate lighting, and cleanliness and material issues affect the user experience. This research aims to redesign the workspace using an interior ecological approach to create a sustainable, ecological, and modern environment. The design method employs a five-stage design thinking approach: Empathize, Define, Ideate, Prototype, and Test. In the discussion, aspects of interior ecological approach such as spatial organization, material usage, lighting, waste management, electromagnetic emissions, indoor pollution, ventilation, and chemical and biological attacks are analyzed. The result is a redesigned co-working space that optimizes the user experience while considering environmental sustainability. Keywords: Co-working space; re-design: interior ecology; sustainable design, design thinking Abstrak — Co-working space menjadi solusi populer bagi individu dan perusahaan yang mencari lingkungan kerja yang dinamis. Namun, Co-working Space SUB Co Spazio di Surabaya menghadapi tantangan terkait kenyamanan dan situasi kerja yang kurang mendukung. Kurangnya fasilitas pendukung, pencahayaan yang tidak memadai, serta masalah kebersihan dan material mempengaruhi pengalaman pengguna. Penelitian ini bertujuan untuk merancang kembali ruang kerja tersebut dengan pendekatan ekologi interior untuk menciptakan lingkungan yang berkelanjutan, ekologis, dan modern. Metode perancangan menggunakan pendekatan design thinking dengan lima tahap: Emphatize, Define, Ideate, Prototype, dan Test. Dalam pembahasan, aspek pendekatan ekologi interior seperti organisasi ruang, penggunaan material, pencahayaan, manajemen sampah, emisi elektromagnetik, polusi dalam ruang, penghawaan, serta serangan kimia dan biologis dianalisis. Hasilnya adalah re-desain co-working space yang mengoptimalkan pengalaman pengguna sambil memperhatikan keberlanjutan lingkungan. Kata Kunci: Co-working space; re-desain; ekologi interior; desain berkelanjutan; design thinking.